Analyzing Awareness Towards Digital Marketing Tools - Abraham, Nimmy K.; Sumathi , Dr. V (International Journal of Accounting and Economics Studies, 2025)
Also, there has been a sharp increase in the number of web clients. Digital marketing has seen significant growth. There are parts of ‎the instruments open in the showcase for advanced items and services. This article discussed the awareness level of individuals ‎towards computerized promotional devices. The data were collected using a questionnaire from 179 respondents living in Ernakulam District in ‎Kerala. Based on the result, most of the respondents are aware of the concept. From the comes about, Social media marketing is the most ‎recognizable device. Google advertisements are the most utilized showcasing tool. Based on the outcomes, the younger generation has ‎more information about digital marketing tools than the older generation‎.
Keywords: Digital Marketing; Search Engine Marketing; Social Media Marketing; Search Engine Optimization; Affiliate Marketing; E- Mail Marketing; ‎Content Marketing.